Inter-generational thoughtfulness in a dynamic public good experiment - Jörg Spiller; Friedel Bolle (European University Viadrina, Department of Business Administration and Economics, 2016)
In a laboratory experiment we investigate inter-generational concerns and myopia in a dynamic Public Good game. Groups of four played a 15-period game where they could either invest in a green sector or in a more profitable brown sector that builds a pollution stock. We find that subjects are more cooperative when their final pollution stock will be inherited by another group in a later session. Furthermore, we observe that defection from a negotiated common plan is higher when subjects are in a loss frame, negotiated plans are more ambitious. We analyze our results in reference to several social preference theories and find that Linear Altruism is most supported in such a dynamic environment.
Keywords: H41; C91; 330; Dynamic; Environmental Economics; Experimental Economics; Inter-Generation; Public Good